(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Growing interest of scientists to question of the scientific presentation technology is reported in this article. The authors note the importance of this interdisciplinary discipline as «the technology of scientific presentations» in the curriculum of universities provided by the linguistic course «Technology of preparation of the scientific text». The main idea of the article is to ensure that all the diversity of the presenting activity features in the field of scientific communication needs special study. Therefore, the object of study seems to be scientific communication, and the subject is its form and specificity for the technology of scientific presentation as an applied discipline in practice.